Interferon-gamma directly affects barrier function of cultured intestinal epithelial monolayers. - J L Madara; J Stafford (The Journal of Clinical Investigation, 1989)
Although epithelia, which often are in intimate contact with lymphoid cells, may bear receptors for various cytokines, it is unclear whether cytokines directly effect epithelial function. We examine the effects of the cytokine interferon (IFN) on barrier function of cultured monolayers of the T84 human intestinal epithelial cell line. Gamma IFN, in concentrations and exposures required to show its other biological effects, directly affects such monolayers. Monolayer resistance is substantially diminished by gamma IFN. Such effects were not due to cytotoxicity as judged morphologically and by LDH assays. Solute fluxes and dual Na+-mannitol flux analysis indicate that the resistance decrease is due to an effect of gamma IFN on tight junction permeability. The effects of gamma IFN on monolayer barrier function were not duplicated by the cytokines interleukin 1, interleukin 2, or tumor necrosis factor. We speculate that such products of activation of lymphoid cells might influence barrier function of intestinal, and perhaps other epithelia in disease states. Images